A pragmatic analysis of humor expressed by Raditya Dika in the Stand Up Comedy - nabila muflihani; Dian Luthfiyati; Riryn Fatmawati (Jurnal Penelitian Humaniora, 2022)
This study was conducted to observe the phenomenon of language that creates humor in Stand up Comedy. The researcher aims to analyze the maxims that are violated to create humor, describe and explain the forms of humor that are created through the violation of the maxims, and explain the function of the humor created through the violation of the maxims in Stand up. Comedy Raditya Dika (SCURD). This research was conducted using mixed methods, a combination of qualitative and quantitative methods. This data source is in the form of Stand up Comedy Raditya Dika in a Youtube video. The researcher is the main instrument of this research, while the data sheet is used as a secondary instrument. After being collected, the data were categorized and analyzed based on the types of violation of maxims, forms of humor, and functions of humor. To increase confidence, the data were triangulated by linguistic experts and students interested in the field.Keywords: pragmatics, humor, maxim flouting, Stand up Comedy.